OPPORTUNITIES FOR DEVELOPING STUDENTS' PROFESSIONAL COMPETENCES USING IMITATION MODELS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the possibilities of developing students' professional competence using simulation models. Interactive and practical approaches are important in modern education, and simulation models are an effective tool for creating an educational process that is close to real working conditions. The article highlights how these models affect the development of students' critical thinking, decision-making skills, and the ability to work independently. The application of artificial intelligence and virtual reality technologies in simulation education is also discussed.